Financial planning : its importance and contribution for the management of cooperative enterprises - Reisdorfer, Vitor K. (2021)
Fil: Reisdorfer, Vitor K. Universidad Regional Integrada del Alto Uruguai e das Missoes. Ciencias Contables y Administración; Brasil.